Universities΄ funding in the framework of the current global financial crisis: Threat or opportunity for the implementation of Triple Helix Theory? - Chrysanthi Balomenou; Konstantinos kolovos (European Regional Science Association (ERSA), 2013)
This work attempts to examine how the global financial crisis has affected the education sector and more specifically, universities. So our paper examines the universities public funding especially in Europe, the mobility of teaching staff, students etc. Also the impact of the financial crisis on universities private sources funding and to mention the need to straighten the collaboration of universities with industries. Universities they have a major role in the economy of a country. They are the main tool for innovation which leads in business development and growth and can reinforce the endogenous regional economic growth. In this view, we present briefly the Triple Helix Theory, which focuses on the importance of the cooperation between public sector, industries and universities. Furthermore, in the theoretical part of our paper, we are examining the case of Greece. More specifically, we are presenting the current situation in Greek Higher Education, focusing on the New Educational Law and especially on the under consultation plan ?Athena? of the Ministry of Education, for the restructure / reallocation of the Greek Universities and Technological Institutions. In the empirical part of our paper, we try to identify whether the Triple Helix Theory is applied in practice or not in Greek case. Our research methodology, based on the data extracted from targeted questionnaires addressed both to Greek entrepreneurs and Greek universities ? Scientific Institutions, attempts to show on one hand how the Universities assess the business environment and their new role in the relevant new institutional framework and on the other hand how the Greek industries evaluate their cooperation with the universities sector and their new role in terms of supporting the local entrepreneurship, as well. The used method for analyzing the results is the one of SPSS (descriptive statistics, correlation ? convexity indicators). The main findings coming by the processing of the statistical data of our scientific research, reveals that in crisis period the universities can find a new source of funding by ?advertising? their main mission, which is the diffusion of Knowledge, and especially, the innovative one that enterprises need, in order to succeed and to overcome the crisis bad effects. Thus, we can observe that the results of our empirical analysis are strongly related to the relevant literature presented in the theoretical our paper. Finally, considerable general conclusions, policy proposals and questions/ challenges for further research will be presented at the end of our study.
Keywords: H52; H75; I23; O31; O43; R11; L26; 330; Universities; Scientific Institutions; Public Funding; Private Funding; Triple Helix Theory; Local Entrepreneurship; Endogenous regional growth